Education On The Accuracy Of Diagnosis And Procedure Codes Regarding Jkn Claim Eligibility At Natama Hospital In 2025 - apriana, ana -; Marbun, Viktor Edyward (INSTITUT KESEHATAN DELI HUSADA, 2025)
According to the Minister of Health Regulation Number 24 of 2022 concerning His study aims to analyze the relationship between the accuracy of diagnostic codes (ICD-10) and procedural codes (ICD-9) with the eligibility of National Health Insurance (JKN) claims at RSU Natama Tebing Tinggi. Ineligible or pending JKN claims are often caused by coding errors that do not comply with ICD guidelines. This research employs a quantitative approach with the Spearman Rank correlation analysis method, as the data did not follow a normal distribution based on the Kolmogorov-Smirnov test. The results of the study indicate a strong and significant relationship between the accuracy of ICD-10 code assignments and claim eligibility (r = 0.746; p = 0.000), as well as a very strong and significant relationship between the accuracy of ICD-9 code assignments and claim eligibility (r = 0.825; p = 0.000). Most JKN claims were declared eligible by BPJS Health verifiers, although a small portion of claims were pending due to inaccurate coding or missing documentation. These findings highlight the importance of improving coders' competencies and validating coding before claim submission. Hospitals also need to develop integrated information systems that can detect coding inconsistencies and strengthen interdepartmental coordination in the claim management process.